Effect of Singing Method Counseling on How to Brush Teeth on Debris Index Values in Visually Impaired Children - Marselin Nainil Afifa; Sri Hidayati; Sunomo Hadi; Ratih Larasati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Visually impaired children are children with special needs who experience partial or total blindness, visually impaired children themselves have limitations to receive stimulation from their senses. The impact of these obstacles is that they pay less attention to dental health and neglect their dental care, one of which is brushing their teeth. One of the efforts that can be done is to conduct counseling with the singing method on how to brush teeth. The problem in this study is the high value of debris index in blind children at SDLB-A YPAB Surabaya is still in the poor category. This study aims to determine the effect of the singing method on how to brush teeth on the value of the debris index in visually impaired children at SDLB-A YPAB Surabaya. This type of research is Quasy Experiment design with pre post design, with a population of 34 visually impaired children. The data collection instrument used is an observation sheet. The data analysis technique uses the Wilcoxon test. The results showed that there was a significant effect of singing method counseling on how to brush teeth on the value of the debris index in blind children at SDLB-A YPAB Surabaya in 2024.